Fluorinated Ionic Liquids as Task-Specific Materials - Vieira, Nicole S. M. (2021)
This chapter is focused on the massive potential and increasing interest on Fluorinated Ionic Liquids (FILs) as task-specific materials. FILs are a specific family of ionic liquids, with fluorine tags equal or longer than four carbon atoms, that share and improve the properties of both traditional ionic liquids and perfluoro surfactants. These compounds have unique properties such as three nanosegregated domains, a great surfactant power, chemical/biological inertness, easy recovery and recyclability, low surface tension, extreme surface activity, high gas solubility, negligible vapour pressure, null flammability, and high thermal stability. These properties allied to the countless possible combinations between cations and anions allow the design and development of FILs with remarkable properties to be used in specific applications. In this review, we highlight not only the unique thermophysical, surfactant and toxicological properties of these fluorinated compounds, but also their application as task-specific materials in many fields of interest, including biomedical applications, as artificial gas carries and drug delivery systems, as well as solvents for separations in engineering processes.